Nya perspektiv: drönarteknologi för landskapsarkitekter - Wingård, Philip (2022)
As consumer grade drones are becoming increasingly accessible and technically refined, a growing number of professionals are taking advantage of the capabilities offered by drone technology. The potential for landscape architecture may seem obvious and the possibilities of seeing the world from above, at the user's convenience, should make it a tool sought-after by landscape architects. It is the author's view however, that implementation, at least in a Swedish context, is slow compared to related fields. As literature on the topic (in relation to landscape architecture) is sparse, the aim of the thesis is to shed light on some of the possibilities offered by drone technology, in particular those related to photogrammetry. A brief overview of the current legal and regulatory aspects of using drones and the resulting products is also included. The author gives examples of how the technology can be used and presents results from experience and exploration of the tool conducted as part of this project. Finally, discussions on the actual utility of the tool, and some thoughts on the implications of a wider use of drones are raised.